CERIA (Smart and Joyful Learning Together): Cultural Education through Regional Songs for PMI Children in Malaysia - Ariel Sucipto; Siti Nur Azizah (Universitas Muhammadiyah Purwokerto, 2025)
Indonesian Migrant Workers’ (PMI) Children in Malaysia face significant barriers to accessing formal education due to their parents’ undocumented immigration status. This condition adversely affects their basic literacy skills, cultural understanding, and the development of national identity. In response to these challenges, the CERIA Program (Cerdas dan Riang Belajar Bersama / Smart and Joyful Learning Together) was developed, targeting PMI children in grades 1–2 who are not served by formal education. The program employs a learning approach that combines traditional Indonesian songs and interactive games, incorporating cultural values. Its methods are grounded in the principles of learning through play and thematic education, with core activities involving the introduction of the song “Ampar-Ampar Pisang” and a musical game designed to engage cognitive, affective, and psychomotor domains. Observations indicate that children demonstrated high enthusiasm, increased self-confidence, and a strong emotional connection to Indonesian culture. The program effectively created a fun, inclusive, and adaptable learning environment for the diaspora community. Therefore, CERIA presents an alternative model of culturally grounded non-formal education suitable for PMI children and other marginalized groups.